Optimization of public health through counseling on diabetes mellitus - Suprapto Suprapto; Chaedyr Iqbal; Qalbia Muhammad Nur (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
Counseling on diabetes mellitus is key in optimizing public health. Diabetes mellitus is a chronic disease that affects millions of people around the world, with serious impacts on health and quality of life. Counseling aims to increase public understanding of diabetes mellitus, including risk factors, symptoms, prevention, and management. In this counseling, we present information about a healthy diet, the importance of regular exercise, and regular blood glucose monitoring. We also highlight the importance of regular medical checkups, stress management, and understanding medication use. In addition, counseling on potential complications of diabetes mellitus, such as heart disease, visual impairment, and nerve damage, is very important to raise public awareness. Effective outreach methods include the use of easy-to-understand educational materials, interactive Q&A sessions, practical demonstrations, and the provision of information through social media and printed materials. By actively involving the public, it is hoped that awareness about diabetes mellitus will increase and appropriate prevention and management measures can be taken. Through this outreach effort, it is hoped that people will have better knowledge about diabetes mellitus, adopt a healthy lifestyle, and adopt behaviors that support the prevention and management of this condition. Thus, counseling about diabetes mellitus becomes an important means in efforts to optimize public health.